Perbedaan hitung trombosit, Mean Platelet Volume (MPV), dan Platelet Distribution Width (PDW) antara pasien dengan infeksi Helicobacter pylori positif dan negatif di RSUP H. Adam Malik, Medan, Indonesia - Fauzan Indra M Lubis; Ricke Loesnihari; Taufik Sungkar (DiscoverSys Inc., 2019)
Background: H. Pylori cause one of the most common human infections, being present in the gastric mucosa of more than a half of the world population. H. pylori infection can be detected by testing antibodies (IgA and IgG) in serum or saliva. Platelets play an important role in the pathogenesis of abnormalities associated with local or systemic inflammation through the release of thrombotic and inflammatory agents. Mean Platelet Volume (MPV) has long been known as a marker of inflammation and this role has been shown previously in various gastrointestinal disorders. Platelet distribution width (PDW) is a platelet index that reflects variations in platelet size.Methods: Thirty-two consecutive dyspepsia patient who fulfilled the criteria were included. Platelet levels, MPV, PDW, are promising in each patient. We changed the differences in platelets, MPV, PDW patients, dyspepsia with positif and negatif H. pylori infection. Data were analyzed using SPSS version 20 for windows.Results: Most of respondents were females (71.9%) and 56±17.45 years old for the average age. The mean of hemoglobin level was 13.47±1.59 g/dL, followed by 11,33±1,71 fL for MPV, 10,7±0,75fL for PDW, and positif H.pylori infection in 56,3% of respondents. There were no differences in platelets, MPV, PDW significantly between the population groups of H. pylori positif and H. pylori negatif (P>0.05)Conclusion: There were no differences in platelets, MPV, PDW significantly between the population group H. pylori positif and H. pylori negatif.